Autism or atypical autism in maternally but not paternally derived proximal 15q duplication. - Cook, E H (1997)
Duplications of proximal 15q have been found in individuals with autistic disorder (AD) and varying degrees of mental retardation. Often these abnormalities take the form of a supernumerary inverted duplicated chromosome 15, more properly described as an isodicentric chromosome 15, or idic(15). However, intrachromosomal duplications also have been reported. In a few cases, unaffected mothers, as well as their affected children, carry the same duplications. During the course of the genotyping of trios of affected probands with AD and their parents, at the positional candidate locus D15S122, an intrachromosomal duplication of proximal 15q was detected by microsatellite analysis in a phenotypically normal mother. Microsatellite and methylation analyses of the pedigree in the following report show that, among three children, the two with autism or atypical autism have maternal inheritance of a 15q11-q13 duplication whereas the third child, who is unaffected, did not inherit this duplication. Their mother's 15q11-q13 duplication arose de novo from her father's chromosomes 15. This finding documents, for the first time, the significance of parental origin for duplications of 15q11-q13. In this family, paternal inheritance leads to a normal phenotype, and maternal inheritance leads to autism or atypical autism.